Genetic Organization of the Oligopeptide Permease (opp) Locus of Salmonella typhimurium and Escherichia coli - Hogarth, Barbara G. (1983)
The opp locus of Salmonella typhimurium and Escherichia coli encodes the oligopeptide permease. In this study we showed by complementation analysis that the locus in both species consists of four separate genes, which we named oppA, oppB, oppC, and oppD. These genes are organized as a single operon. The direction of transcription was determined.